(untitled) (Research, Society and Development, 2025)
Dysbiosis of the intestinal microbiota plays an important role in the development of diseases such as ulcerative colitis and Crohn’s disease. Thus, turmeric longa can help in the treatment of these diseases, due to its anti-inflammatory and antioxidant action. The objective of the study was to analyze the consumption of turmeric longa in people with inflammatory bowel diseases, verify the reduction of side effects with the use of turmeric and report its effects on gastrointestinal health. The methodology is a literature review study taking into account an analysis of scientific articles that address the topic exposed in the EBSCO, CAPES and PubMed databases. National and international studies in English and Portuguese, from the last 10 years, were selected. The search methodology was carried out using the following descriptors: (curumim AND dysbiosis) OR (curumim and intestine) OR (curumim AND inflammation). After analyzing the studies, it was found that this herbal medicine had a preventive action on the intestinal inflammatory response, repairs the intestinal microbiota and can prevent early infections by bacteria, enriching the diversity of the intestinal microbiota. This study allowed us to understand that turmeric longa can treat inflammatory bowel diseases by modulating the intestinal microbiota, but requires further studies.